Neonatal Appendicitis and Incarcerated Inguinal Hernia: Case Report and Review of the Literature - Fascetti-Leon, Francesco (J Indian Assoc Pediatr Surg, 2017)
Neonatal appendicitis carries a high mortality rate. We describe a peculiar case presented after an incarcerated hernia manually reduced in a 4-week-old male neonate with ipsilateral undescended testis. Laparoscopy allowed a prompt recognition of an unexpected intra-abdominal life-threatening condition. Pathogenesis, treatment, and outcome are discussed on the light of a comprehensive literature review.